Dosimetric effects of respiratory motion during stereotactic body radiation therapy of lung tumors. (3rd August 2022) - Sarudis, Sebastian; Karlsson, Anna; Nyman, Jan; Bäck, Anna
Abstract: Background: Respiratory-induced lung tumor motion may affect the delivered dose in stereotactic body radiation therapy (SBRT). Previous studies are often based on phantom studies for one specific treatment technique. In this study, the dosimetric effect of tumor motion was quantified in real patient geometries for different modulated treatments and tumor motion amplitudes for lung-SBRT. Material and Methods: A simulation method using deformable image registrations and 4-dimensional computed tomographies (4DCT) was developed to assess the dosimetric effects of tumor motion. The method was evaluated with ionization chamber and Gafchromic film measurements in a thorax phantom and used to simulate the effect for 15 patients with lung tumors moving 7.3–27.4 mm. Four treatment plans with different complexities were created for each patient and the motion-induced dosimetric effect to the gross tumor volume (GTV) was simulated. The difference between the planned dose to the static tumor and the simulated delivered dose to the moving tumor was quantified for the near minimum (D98% ), near maximum (D2% ) and mean dose (Dmean ) to the GTV as well as the largest observed local difference within the GTV (Maxdiff ). Results: No correlation was found between the dose differences and the tumor motion amplitude or plan complexity. However, the largest deviations were observed for tumors moving >15.0 mm. The simulated delivered dose was within 2.5% from the planned dose for D98% (tumors moving <15 mm) and within 3.3% (tumors moving >15 mm). The corresponding values were 1.7% vs. 6.4% (D2% ); 1.7% vs. 2.4% (Dmean ) and 8.9% vs. 35.2% (Maxdiff ). Using less complex treatment techniques minimized Maxdiff for tumors moving >15.0 mm. Conclusion: The dosimetric effects of respiratory-induced motion during lung SBRT are patient and plan specific. The magnitude of the dosimetric effect cannot be assessed solely based upon tumor motion amplitude or plan complexity.